Alteration of the fecal microbiota in Chinese children with autism spectrum disorder. Issue 6 (11th April 2022) - Xie, Xinyan; Li, Li; Wu, Xiaoqian; Hou, Fang; Chen, Yanlin; Shi, Liuwei; Liu, Qi; Zhu, Kaiheng; Jiang, Qi; Feng, Yanan; Xiao, Pei; Zhang, Jiajia; et al.
Abstract: Autism spectrum disorder (ASD) is associated with altered gut microbiota. However, there has been little consensus on the altered bacterial species and studies have had small sample sizes. We aimed to identify the taxonomic composition and evaluate the changes in the fecal microbiota in Chinese children with ASD by using a relatively large sample size. We conducted a case–control study of 101 children with ASD and 103 healthy controls in China. Demographic information and fecal samples were collected, and the V3‐V4 hypervariable regions of the bacterial 16S ribosomal RNA (rRNA) gene were sequenced. The alpha and beta diversities between the two groups were significantly different. After correcting for multiple comparisons, at the phylum level the relative abundances of Actinobacteria and Proteobacteria in the case group were significantly higher than those in the control group. The relative abundance of the Escherichia ‐ Shigella genus in the case group was significantly higher than that of the control group, and the relative abundance of Blautia and unclassified_f__Lachnospiraceae in the control group were higher than that of the case group. Phylogenetic Investigation of Communities by Reconstruction of Unobserved States analysis showed that children with ASD may have disturbed functional pathways, such as amino acid metabolism, cofactor and vitamin metabolism, and the AMP‐activated protein kinase signaling pathway. This study revealed the characteristics of the intestinal flora of Chinese children with ASD and provided further evidence of gut microbial dysbiosis in ASD. Lay Summary: This study characterized the gut microbiota composition of 101 children with ASD and 103 healthy controls in China. The altered gut microbiota may contribute significantly to the risk of ASD, including significant increases in the relative abundances of Actinobacteria, Proteobacteria and Escherichia ‐ Shigella and significant decrease of Blautia and unclassified_f__Lachnospiraceae . This study provided further evidence of gut microbial dysbiosis in ASD.